(untitled) (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: Laparoscopy is perceived as a minimally invasive surgical technique that both provides a panoramic & magnified view of the pelvic organs and allows surgery at the time of diagnosis. Laparoscopy has became an integral part of gynaecologic surgery for the diagnosis and treatment of abdominal and pelvic disorders of the Female reproductive organs. Endoscopic reproductive surgery intended to improve fertility many includes surgery of the uterus, ovaries, pelvic peritoneum and the fallopian tubes. Aim: To determine the best treatment for infertility. Method: The prospective study was carried out among the infertile women during the period of July 2014 to December 2014, in Shaheed Suhrawardi Medical College Hospital. Fifty women identified with Infertility both primary and secondary with the criteria of menstrual cycles with duration of 25-45 days were selected. Semen analysis was considered to be normal. Result: Fifty women underwent diagnostic & therapeutic laparoscopy between the period of July 2014 to December 2014. Among them 20 suffered from primary subfertility & 30 from secondary subfertility. In primary subfertility 12 patients were diagnosed as poiycystic ovarian disease & 7 patients diagnosed as minimal to moderate endometriosis 1 patient diagnosed as pelvic inflammatory disease. In secondary subfertility 15 patients diagnosed as pelvic inflammatory disease, 12 patients with endometriosis & 03 patients as poiycystic ovarian disease. Therapeutic intervention were done in almost all cases of subfertility. Conclusion: The routine use of diagnostic laparoscopy for the evaluation of all case of female infertility is currently under debate. Current evidence indicates that the surgical treatment of minimal or mild endometriosis increase the spontaneous pregnancy rate in Infertility women J Shaheed Suhrawardy Med Coll, December 2015, Vol.7(2); 73-75